Crime and misconduct in sport - Engelberg, T.; Moston, S. (Sport in Society: Cultures, Commerce, Media, Politics, 2020)
The global pandemic of 2020 brought about the suspension of almost all sporting activity. From grassroots sport through to elite competitions, the sporting world effectively ended. At the time of writing (early May 2020), there are tentative plans to restart some elite competitions, with the German Bundesliga and the Australian National Rugby League both announcing that competitions will recommence shortly. In both cases, the plan is to play games for a television audience only, in near-empty stadiums. In the months and years to come, it is likely that Sport in Society will see considerable debate as to the logistical problems in restarting sporting competition during and after a pandemic. For example, as spectators will not be able to attend matches and so there will be no game-day revenues. The purpose of competing is almost entirely to fulfil contractual obligations to television companies and sponsors, not because of any consideration for fans. It is also likely that the journal will see considerable debate as to the social and ethical problems of recommencing sporting competitions. For example, whilst players will need to be tested for COVID-19 on a regular basis, tests for first responders (medical staff, police, etc.) are currently in short supply.